Transport Et Approvisionnement Des Produits Vivriers A Abidjan En Côte d’Ivoire - Hélène-Francette, Kouassi Mangoua Akissi; Eric, Koffi Lath Franck; Jérôme, Aloko N’guessan (European Scientific Journal, ESJ, 2017)
The population of Abidjan is growing rapidly. This demographic mass creates a food needs. To answer this demand, transport service is essential to reach the production areas. The contribution explains an overview of the transport service in a supply chain of food to Abidjan. The methodology research is based on two facts: the bibliographic research and field surveys. The study shows the meaning of transport which may vary according to the scales and levels of supply. Difficult conditions to access production sites, road traffic harassment and degradation of road infrastructure significant are problems faced by transporters in carrying out their activities.